2022
DOI: 10.1098/rstb.2021.0309
|View full text |Cite
|
Sign up to set email alerts
|

Flexible use of contact calls in a species with high fission–fusion dynamics

Abstract: The ‘social complexity hypothesis' posits that complex social systems (which entail high uncertainty) require complex communicative systems (with high vocal flexibility). In species with fission–fusion dynamics, where the fluid composition of temporary subgroups increases the uncertainty with which group members must manage their social relationships, vocal communication must be particularly flexible. This study assessed whether contact call rates vary with caller and audience characteristics in free-living sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…Indeed, we found that social factors appear to be influencing juveniles during an early stage of vocal development: call combination production varies with the number of other juvenile group members, in addition to the group adult sex ratio. Other studies have found that social interactions with conspecifics can influence vocal development [41,[81][82][83], and our study provides evidence to suggest this is the case for call combination production in magpies. Interestingly, our results suggest that group size does not affect juvenile callers in the same way it does adult callers: group size does not correlate with variation in juvenile call combination frequency or diversity.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, we found that social factors appear to be influencing juveniles during an early stage of vocal development: call combination production varies with the number of other juvenile group members, in addition to the group adult sex ratio. Other studies have found that social interactions with conspecifics can influence vocal development [41,[81][82][83], and our study provides evidence to suggest this is the case for call combination production in magpies. Interestingly, our results suggest that group size does not affect juvenile callers in the same way it does adult callers: group size does not correlate with variation in juvenile call combination frequency or diversity.…”
Section: Discussionsupporting
confidence: 80%
“…Several functions, all related to socio-spatial coordination within a group and not mutually exclusive, have been proposed. For some authors, these calls would have a determinant role in the initiation and/or regulation of group movements (Neumann and Zuberbühler, 2016;Sperber et al, 2017), in the coordination of subgroup fusions (Briseño-Jaramillo et al, 2022), or would allow for maintained contact between isolated or distant individuals by giving spatial indications (Digweed et al, 2007;Snowdon and Hodun, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Spider monkeys exchange a variety of signals, including facial expressions, short-lasting contacts, long-lasting contacts and vocalizations [4951]; for a detailed treatment of vocalizations see [52]. In many primate species, grooming is an affiliative signal [53], reflecting the value and compatibility of social relationships [15].…”
Section: The Communicative Toolkitmentioning
confidence: 99%